'The teacher said I'm thick!' Experiences of children with Attention Deficit Hyperactivity Disorder within a school setting. Issue 2 (May 2016) - Kendall, Lynne
Abstract : Children and young people who have been diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) can often experience difficulties within an education setting. ADHD can impact upon their educational achievements and subsequent future employment. This paper draws upon data gathered from a small scale study and has sought to elicit the 'voice' of young people who have ADHD and their experience within a school setting. Findings of this study indicate that there is a need for teachers to be more informed about the impact that ADHD can have on a pupil and teachers need to develop positive strategies to support these individuals within the classroom. Ideally, adequate training around ADHD should begin within initial teacher training prior to entering the teaching profession.